The Marketing Strategy and Benefits Analysis of Papringan Market in Indonesia: A Narrative Review of Literature - Sekar Aji Widyastiti; Elsa Ternanda Alsyifa; Retno Bagus Sayekti; Zulfikar Bagus Pambuko (Urecol Journal. Part H: Social, Art, and Humanities, 2022)
Traditional market development is essential to survive competition in modern markets. Furthermore Papringan, one of Indonesia's traditional viral markets, implemented a strategy of hawking traditional food with keping pring as a currency. This study examines the marketing concept of Papringan Market, Temanggung, and its economic impact on the community. It conducted a narrative review with two steps, including database search and thematic analysis. The study is limited to Indonesian and publication in the last five years (2015-2020). An electronic database search from Google Scholar and ResearchGate obtained 28 articles, though only nine met the inclusion criteria. The result indicated that the marketing strategy involves implementing keping pring as a currency, selling vintage foods, traditional presentations, developing websites, making motion graphics, and utilizing social media, specifically Instagram. Furthermore, the market functions as the basis for economic welfare, improving the human resources, environmental conservation, and building brotherhood.